NEW STRATEGIES FOR THE PREVENTION OF RSV INFECTIONS IN CHILDREN – A REVIEW ARTICLE - Gwiaździńska, Oktawia; Strzykała, Anita; Lewandowski, Jakub; Szlegiel, Igor; Myszak, Denis (International Journal of Innovative Technologies in Social Science, 2026)
Background: Respiratory syncytial virus (RSV) is a leading cause of lower respiratory tract infections in infants and young children worldwide, contributing substantially to hospitalizations, healthcare utilization, and long-term respiratory morbidity. Despite decades of preventive efforts, RSV remains a major public health burden, particularly in high-risk populations.Objective: To review current and emerging strategies for the prevention of RSV infection in children, including traditional passive immunoprophylaxis, next-generation monoclonal antibodies, and maternal vaccination during pregnancy.Methods: A narrative review of key clinical trials, systematic reviews, and guideline-based recommendations was conducted, focusing on evidence supporting palivizumab, nirsevimab, and maternal RSV vaccination. Data from pivotal randomized controlled trials and real-world studies were synthesized.Results: Palivizumab, a monoclonal antibody targeting the RSV fusion (F) protein, has demonstrated a reduction in RSV-related hospitalizations of approximately 50–55% in high-risk infants, but its use is limited by cost and repeated dosing requirements. Nirsevimab, a long-acting monoclonal antibody, provides season-long protection after a single dose and has shown a reduction of up to 74.5% in medically attended RSV lower respiratory tract infections, with additional evidence from real-world studies confirming reduced hospitalization rates. Maternal RSV vaccination has been shown to confer passive immunity to infants through transplacental antibody transfer, significantly reducing severe RSV disease and hospitalization in early infancy, with a favorable safety profile.Conclusions: Advances in RSV prevention have shifted clinical practice from targeted prophylaxis in high-risk infants toward broader population-based strategies. Long-acting monoclonal antibodies and maternal vaccination represent complementary and highly effective approaches with the potential to substantially reduce RSV-associated morbidity, hospitalizations, and healthcare burden globally.